Catalytic Biomimetic Asymmetric Reduction of Alkenes and Imines Enabled by Chiral and Regenerable NAD(P)H Models - Wang, Jie; Zhu, Zhou‐Hao; Chen, Mu‐Wang; Chen, Qing‐An; Zhou, Yong‐Gui (Angewandte Chemie International Edition, 2019)
The development of biomimetic chemistry based on the NAD(P)H with hydrogen gas as terminal reductant is a long‐standing challenge. Through rational design of the chiral and regenerable NAD(P)H analogues based on planar‐chiral ferrocene, a biomimetic asymmetric reduction has been realized using bench‐stable Lewis acids as transfer catalysts. A broad set of alkenes and imines could be reduced with up to 98 % yield and 98 % ee, likely enabled by enzyme‐like cooperative bifunctional activation. This reaction represents the first general biomimetic asymmetric reduction (BMAR) process enabled by chiral and regenerable NAD(P)H analogues. This concept demonstrates catalytic utility of a chiral coenzyme NAD(P)H in asymmetric catalysis. Through rational design of chiral and regenerable NAD(P)H analogues based on planar‐chiral ferrocene, a biomimetic asymmetric reduction has been realized using bench‐stable Lewis acids as transfer catalysts. A broad set of tetrasubstituted alkenes and imines could be reduced with up to 98 % yield and 98 % ee. This protocol represents the first general biomimetic asymmetric reduction process enabled by NAD(P)H analogues.